STRATEGY OF THE GASTROPOD MOLLUSK PUGILINA TUPINIQUIM (MELOGENIDAE) TO AVOID ENVIRONMENTAL STRESS DURING LOW TIDE - da Silva, Ellano José; de Oliveira, Ítala Alves; Garcia, Frederico Alekhine Chaves (Seven Editora, 2026)
This study investigated the distribution and size patterns of the gastropod mollusk Pugilina tupiniquim in relation to different degrees of exposure in the Pacoti Estuary, Ceará. Variations in density and size of mollusks were found among the sampled points. The results highlighted a higher density of smaller individuals in locations less exposed to sunlight, desiccation, and predation. The presence of the species in different substrate types suggests a relationship with the abundance of its prey, especially bivalves such as Anomalocardia flexuosa. These results contribute to a better understanding of the ecology of P. tupiniquim in estuarine ecosystems.